Prognostic factors influencing anatomical and functional outcome of Myringoplasty (Bangladesh Journal of Otorhinolaryngology, 2013)
Objective: To assess the rate of healing of tympanic membrane, hearing status before and after operation and determine the factors influencing surgical outcome. Methods: This cross-sectional study was done in the department of Otolaryngology & Head- Neck Surgery of SSMC & Mitford Hospital, Dhaka, during the period of January, 2008 to December, 2009. A total of 60 patients was underwent myringoplasty operation and taken detailed history, clinical findings and post operative assessment. Analyzed data presented by various tables, graphs and figures. Results: The study included 60 patients of myringoplasty operation. Age of the patient was between 15-45 years. Out of 60 patients male was 60% and female was 40%. Highest number of patients was in the age group of 15-25 years. Conclusion: Hearing improvement after myringoplasty in anatomically successful cases improve quality of life of the patient. DOI: http://dx.doi.org/10.3329/bjo.v19i1.14858 Bangladesh J Otorhinolaryngol 2013; 19(1): 18-23